2015
DOI: 10.1371/journal.pone.0128723
|View full text |Cite
|
Sign up to set email alerts
|

Novel Classification of the Posterior Auricular Artery Based on Angiographical Appearance

Abstract: PurposeTo investigate the length variation of the posterior auricular artery and propose a novel classification of the posterior auricular artery based on angiographical appearance.Patients and MethodsA series of 234 consecutive patients who had undergone conventional cerebral angiography was analyzed. The posterior auricular artery was examined on the lateral projection of the external carotid or common carotid arteriography. The posterior auricular artery was classified into four groups by length, using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
0
7
1
1
Order By: Relevance
“…21 However, limited studies have been conducted on its neurosurgical use. Although in 2015, Tokugawa et al 15 coined a novel classification of PAA variations based on the angiographic appearance of 424 subjects, the PAA variation is yet to be discussed for children. On the basis of our study on pediatric patients, classes 3 and 4, the 2 viable candidates for PAA-EDAS, were at 37.5% and 2.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, limited studies have been conducted on its neurosurgical use. Although in 2015, Tokugawa et al 15 coined a novel classification of PAA variations based on the angiographic appearance of 424 subjects, the PAA variation is yet to be discussed for children. On the basis of our study on pediatric patients, classes 3 and 4, the 2 viable candidates for PAA-EDAS, were at 37.5% and 2.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we adopted the PAA classification coined by Tokugawa et al 15 with some modifications. The alphabetic classification was changed to numeric for easier distinction between STA and PAA classes, as well as the anteriority and posteriority of classes 3 and 4 as illustrated in Fig 2 . To evaluate the postoperative technical outcomes of PAA-EDAS and STA-EDAS, we compared the degree of revascularization on follow-up transfemoral cerebral angiography between the PAA-EDAS and STA-EDAS groups based on the Matsushima grade: Grade A denotes revascularization of more than two-thirds of the MCA territory, grade B denotes revascularization of between one-and two-thirds of the MCA territory, and grade C denotes revascularization of a slight amount or none of the territory.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is a contrast to that reported by liu et al who in their study reported that posterior auricular artery crossed the facial nerve below in all their 10 cadaveric dissections. 9,22 We identified stylomastoid artery arising from the posterior auricular artery in all 14 cadaveric dissections. The stylomastoid artery was found to be running below the trunk of facial nerve in all our 14 cadaveric dissections.…”
Section: Discussionmentioning
confidence: 99%
“…Tokugawa et al 15 recently proposed a classification of PAA based on their angiographic appearance; this research was based on angiograms made because of intracranial pathologies to 234 patients. These authors proposes 4 types of PAA with their respective frequency: type A (15.1%), PAA terminates between its origin and the center of the external auditory canal; type B (34.9%), PAA terminates between the center of the external auditory canal and the top of the helix; type C (48.8%), PAA terminates between the top of the helix and the vertex; and type D (1.2%), PAA reaches up to the vertex.…”
Section: Discussionmentioning
confidence: 99%